أثر الرفع على ربحية السهم في المؤسسات الخدمية الجزائرية حالة مؤسسة التسيير الفندقي سلسلة الأوراسي. (مجلة الواحات للبحوث والدراسات, 2015)
The following study deals with the issue of the extent to which the Algerian service enterprises adopt the leverage impact in improving the profitability of the shares. The results show that the enterprises adopt deliberately financial and operational leverage so that they can raise the rate of return on equity through the dependence on financing sources with fixed costs to achieve a high rate of return, in addition to the dependence on production tools with fixed costs to increase earnings per share and then the value of the enterprise as a whole. Considering El Aurassi hotel, there is a high financial leverage ratio which indicates a rise in the financial risks which the enterprise may face, especially that it is mainly based on providing services.The enterprise dependence on production tools with fixed costs resulted in raising the degree of the operational leverage to be a positive one. This means that any change in the enterprise sales lead to an increase in earnings per share. It can be noted that the enterprise under study does not depend on a studying the leverage impact on the profitability of its shares. Key words: financing sources, financial leverage, operational leverage, the rate of return, earnings per share